Ekspresi Keresahan Pemuda melalui Media Sosial: Studi Kritik terhadap Narasi Indonesia Gelap : Expression of Youth Unrest through Social Media: A Critical Study of the Dark Indonesia Narrative - Clairine, Angela; Lestari, Eithar Indah Dewi; Wiyono, Erica Natasha; Wildan R, Muhamman (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2025)
The hashtag Indonesia Gelap is a phenomenon that describes the outpouring of disappointment from the community, especially the youth, towards policies made by the Prabowo-Gibran government, which are considered not pro-community interests and welfare. This phenomenon has developed into a cultural expression in the form of digital criticism in the form of hashtags and demonstrations as a response to perceived structural inequality. This study aims to examine the forms of expression of youth unrest through social media and collective movements, using the literature study method and the relative deprivation theory approach from Ted Gurr. The focus of the analysis is directed at the gap between the expectation of a decent life and the political reality that narrows the space for actualization of the younger generation. The results of the study show that social media is not only a medium of expression, but also an arena for symbolic consolidation that encourages real action. The emergence of hashtags such as #Narasi Indonesia Gelap, #KaburAjaDulu is a form of irony as well as resistance to the official state narrative. This study recommends the importance of formulating policies that are responsive to youth aspirations, as well as the need for open dialogue to reduce the distance between the state and citizens.